Insertion torque and resonance frequency analysis (ISQ) as predictor methods of implant osseointegration - Gutiérrez, Osvaldo Gahona; Marinov, Xenia Granic; Chelmes, Cristina Antunez; Alucema, Stefan Domancic; Díaz Narváez, Víctor Patricio; Abarca, Robert Utsman (Journal of Osseointegration, 2018)
Aim Determining appropriate primary stability at time of implant placement is a key therapeutic decision. The aim of the study was to compare insertion torque and implant stability quotient (ISQ) obtained at the time of implant placement, as predictors of osseointegration. Methods There were 31 implants evaluated in the maxilla and 29 in the mandible. A "High Torque Indicating Ratchet Wrench" was used for the measurement of insertion torque and a "Osstell Mentor®" to register the ISQ value at the end of each surgery. At 6 weeks counter-torque was performed on each implant using a "Low Torque Indicating Ratchet Wrench" applying 20 to 32 Ncm. Successful osseointegration was appropriately obtained with torque insertion of 35 or more and an ISQ of 60 or more without mobility, as well as torque insertion less than 35 and an ISQ less than 60 with mobility. The results, contrary to those described above, were considered to be failure. The use of ROC (Receiver Operating Characteristic) curves establishes differences between the two methods. Contingency tables and Kappa statistics were used to analyze the coincidence results between methods. Insertion torque was used as the Gold Standard. The significance level used is Î±‰¤0.05. Results In the ROC curve analysis, the area of value was 0.611 (p> 0.05). The Kappa statistic value was 0.208 (p> 0.05) and there are no discrepancies between success and failure between the two methods compared. Conclusion Both methods tend to have the same results in relation to the studied variables.